Assessment of a Designed Exercise Program on Physical Capacity Using Six-Minute Walking Test (6MWT) in Hemodialysis Patients - Mansooreh Aliasgharpour; Zahra Hadiyan (Tehran University of Medical Sciences, 2011)
Background & Aim: Hemodialysis patients have reduced physical capacity for various reasons resulting in increased dependence on others. The aim of this study was to investigate the effect of a designed exercise program on physical capacity using the Six-Minute Walking Test (6MWT) in hemodialysis patients. Methods & Materials: In a quasi-experimental design, 25 hemodialysis patients were selected conveniently from three hospitals of Tehran. The patients in the experimental group (n=12) followed a designed exercise program three days per week, which lasted for 8 weeks. The participants in the experimental group had to exercise for 20 minutes immediately after dialysis sessions followed by a 10-minute bed rest and deep slow breaths, with their eyes closed. The control group (n=13) did not receive any treatment. Descriptive and inferential statistics were applied for data analysis using SPSS-18. Results: The difference in the means of the 6MWT was not statistically significant at the start and end of the fourth and eighth weeks of the exercise program in both groups. However, comparison of these values in the experimental group before and after the intervention was clinically significant, although not statistically significant. Conclusion: In this study, physical capacity increased after performing the exercise in the experimental group, but this value was not statistically significant. Further studies are recommended in the field.